Pilonidal Sinus Disease: Risk Factors for Postoperative Complications and Recurrence - Onder, Akin (International College of Surgeons, 2012)
The aim of this study is to analyze the risk factors for complications and recurrence in pilonidal sinus disease. The prospective study consisted of 144 patients with pilonidal sinus disease who were operated on at Dicle University Medical Faculty, Department of General Surgery, between February 2008 and December 2010. Patients receiving the Limberg flap totaled 106 (73.6%), while 38 (26.4%) had primary closure. Postoperative complications developed in 42 subjects (29.2%), and recurrence occurred in 19 (13.2%). The Limberg flap method was statistically considered as a risk factor for postoperative complications (P  =  0.039). Regarding recurrence, family tendency (P  =  0.011), sinus number (P  =  0.005), cavity diameter (P  =  0.002), and primary closure (P  =  0.001) were found to be risk factors. Postoperative complication rate is higher in the Limberg flap method than primary closure method. The risk of recurrence is related to family tendency, sinus number, cavity diameter and anesthesia type and is also higher in primary closure.